Faktor-Faktor Yang Mempengaruhi Rendahnya Kunjungan Balita Di Posyandu Meohai Kabupaten Kolaka Timur - Yenni Yenni; Andi Tenri Angka (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2021)
Posyandu is a form of community empowerment activity which has the benefit of obtaining information on health services, especially the health of children under five and mothers, monitoring the growth of children under five so they are not affected by malnutrition, obtaining vitamin A capsules, and for health education regarding maternal and child health. The aim of the research is to determine the factors - Factors that influence the low number of visits by toddlers to posyandu include the Poli-Polya Health Center in East Kolaka Regency. The type of research used was a cross-sectional study. The samples in the research were all toddlers who came to visit the posyandu at the East Kolaka Regency Poly-Poly Health Center in 2020, totaling 75 toddlers using a total sampling technique. The results of the research show that work is a factor that influences the low number of visits by toddlers to Meohai Posyandu at the Poli-Polya Community Health Center, East Kolaka Regency, where statistical tests using Chi-Square Tests obtained a value of p=0.036<ɑ=0.05, education is a factor that influences the low visits of toddlers to Posyandu Meohai at the Poli-Polya Health Center in East Kolaka Regency where statistical tests using Chi-Square Tests obtained a value of p = 0.028 < ɑ = 0.05, distance from home is a factor that influences the low number of visits by toddlers to Posyandu Meohai at the Poli-Polia Health Center East Kolaka Regency where statistical tests using Chi-Square Tests obtained a value of p = 0.017 < ɑ = 0.05. Advice for mothers of toddlers to increase visits to posyandu and develop knowledge of the importance of visiting toddlers to posyandu.